Effect of short-term Psychiatric Intervention in Cancer Patients - Ashraff, S (Med J Armed Forces India, 2004)
A total of 50 patients undergoing cancer treatment at Malignant Disease Treatment Centre were included in the present study aimed at evaluating the psychological status of cancer patients. All patients filled a specially designed proforma and the following psychological questionnaires : General Health Questionnaire, Carroll Rating Scale for Depression, State-Trait Anxiety Inventory, PGI General Well-being Scale and Quality of Life Scale. Analysis of the results showed that 22 (44%) of the cancer patients had psychiatric disorders and this number had reduced to 12 (24%) after therapy. The difference was statistically significant. Psychiatric treatment also resulted in a statistically significant reduction in level of depression as measured by Carroll Rating Scale for depression. Short term psychiatric treatment was found to be very useful in treating psychiatric morbidity and depression in cancer patients.